218k views
0 votes
????????????????????????

????????????????????????-example-1
User Phoenixo
by
4.8k points

1 Answer

6 votes

Answer:

C. Center (3,-2) and radius 3

Explanation:

The given circle has equation:


x^2+y^2-6x+4y+4=0

We rearrange to get:


x^2-6x+y^2+4y=-4

We add the square of half the coefficients of the linear terms to both sides of the equation:


x^2-6x+(-3)^2+y^2+4y+(2)^2=-4+(-3)^2+(2)^2

We factor the perfect squares and simplify to get;


(x-3)^2+(y+2)^2=9

We can rewrite as;


(x-3)^2+(y--2)^2=3^2

Comparing this to the standard equation of the circle;


(x-h)^2+(y-k)^2==r^2

We have (3,-2) and the center and r=3 as the radius.

User Lohit Gupta
by
5.6k points